MENGGUGAT DIKSI DAN EKSPRESI ANAK PADA PUISI ANAK MAJALAH BOBO - Muhamad Haryanto (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2012)
Child  poem  and  adult  poem  talk  about  life.  However,  they  are  different  in expressing  and  dealing  with it because  they  have  different  maturity  and  point  of view.  Child  expressions  in  poem  vary  from  trivial,  funny,  habit,  nature,  ream, religiosity,  love  and  so  on.  Those  expressions are  conveyed  through  simple dictions.  Bobo  magazine  is  child  magazine  which  give  space  for  literary expressions  specially  child  poems. In  Bobo  child  poems,  there  is  unique expression in choosing diction and variations. Keywords: child poems, expresson, diction, Bobo magazine